PREVALENCE OF VITAMIN D DEFICIENCY AMONG PATIENTS WITH NEWLY DIAGNOSED CHRONIC KIDNEY DISEASE - Muhammad, Ikram; Khursheed , Muhammad; Muhammad, Shad; Muhammad, Noor; Ghulam, Salma; Rehman, Zia ur (Khyber Journal of Medical Sciences, 2022)
Objective: To determine the prevalence of vitamin D deficiency among patient with newly diagnosed chronic kidney disease Methods: It was a descriptive cross-sectional study with consecutive sampling carried out at the division of nephrology lady Reading Hospital Peshawar from July 2019 to December 2019. We measured vitamin D levels in 152 patients with newly diagnosed chronic kidney disease. Results: A total of 152 patients were included in this study. Out of these 85(56%) were male while 67(44%) were female. Mean age was 34 + 12.86 yrs. Duration of CKD was <1y in 109(72%) of patients while 43(28%) had a duration of CKD > 1yr with a mean duration of 1 + 8.42ys and mean weight of 75 + 12.33kgs. Vitamin D deficiency was present in 80% of the patients with newly diagnosed CKD. Conclusions: Our study shows that the incidence of vitamin D deficiency was 80% among patients with newly diagnosed chronic kidney disease.